STUDI KOHABITASI LUTUNG (Trachypithecus auratus) DENGAN MONYET EKOR PANJANG (Macaca fascicularis) DI TAMAN WISATA ALAM KERANDANGAN - Wulandari, Ni Putu Ayu Siva; Syaputra, Maiser; Wahyuningsih, Endah (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Spangled Ebony Langur and Long-tailed Monkey are species of wild animals that have special characteristics, namely having mammary glands, reproducing by giving birth, their bodies covered with fur or hair, and breathing with their lungs. The IUCN has designated the Spangled Ebony Langur species as vulnerable and the Long-tailed Monkey as an endangered species. To prevent this shortage, important and urgent conservation efforts are needed to save these two species. These two primate species were detected using the same habitat in Kerandangan Nature Tourism Park so there is overlap (cohabitation) in this area. This research aims to analyze patterns of habitat use and space use in Spangled Ebony Langur and Long-tailed Monkey as well as analyzing cohabitation between Spangled Ebony Langur and Long-tailed Monkey in Kerandangan Nature Tourism Park. This research uses the roaming method for habitat use and minimum convex polygon for space use. The results of the research show that there is cohabitation between Spangled Ebony Langur and Long-tailed Monkey, the use pattern for food trees has an association value of 0.12, sleeping trees 0.07, and resting trees 0.08. With an overlap in home ranges in the first and second areas of 0.07 and 0.06, in territorial areas in the first and second areas of 0.08, and in core areas in the first and second areas of 0.1 and 0.09. Using vertical space, the results obtained were 0.22. It can be concluded that habitat use and space use as well as cohabitation between the two primates in Kerandangan Nature Tourism Park are low.